El Uso de los Pronósticos de la Variabilidad Climática Estacional para Planificar el Establecimiento de la Plantación de Bosques - Norman Breuer; Matthew Langholtz; David Zierden; Clyde Fraisse (EDIS)
AE464, a 3-page fact sheet by Norman Breuer, Matthew Langholtz, David Zierden, and Clyde Fraisse, is the Spanish language version of ABE354/AE282: Using Seasonal Climate Variability Forecasts to Plan Forest Plantation Establishment. It provides strategies to consider for pine plantation establishment in Florida and southern Alabama and Georgia, where seasonal climate conditions can be better predicted because it is affected by the El Niño Southern Oscillation (ENSO) phenomenon. Includes references. Published by the UF Department of Agricultural and Biological Engineering, July 2010.